Washbasin Design with DFMA Approach for Covid-19 Prevention - Iswanto Iswanto; Ribangun Bamban Jakaria; Boy Isma Putra; Marzuki Ibrahim (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2022)
The Covid 19 pandemic makes the need for a washbasin in a public place to prevent the spread of the virus. However, in practice the available washbasins are still not standardized and not ergonomic. So that in this study an ergonomic washbasin design was tried using the DFMA (Design for Manufacture and Assembly) method. Because using the DFMA method aims to improve the design. Through this method, it is possible to produce products with a shorter time and the number of components that are more effective in accordance with the function but have better design quality. In this study there were several components that were repaired, combined and removed, but did not change the function and usability of these components. So that this research resulted in a sink design that is modern, multifunctional, easy to use and comfortable.